2006
DOI: 10.4028/www.scientific.net/msf.510-511.78
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Antibacterial Activity of Silver Ions-Substituted Hydroxyapatite/Titania

Abstract: In this paper a series of silver ions-substituted hydroxyapatites (HA) were prepared. The antibacterial activities of these materials on textiles against bacteria have been investigated. Titania (TiO2) was selectively added into the materials to decrease the silver-ions concentration to get the same active antimicrobial effects. The microstructure, the shape and size, concentration of silver, and the groups of the composite materials were characterized using transmission electron microscopy (TEM), infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is reported that the water molecules in the inter-lamellar regions can change the overall crystalline state of the PA matrix [32]. On the other hand, the release of the substituted Ag + ions in the HA lattice should be much slower [10,20]; this may be another reason why the Ag + release from the Ag-nHA/TiO 2 /PA66 composite scaffold can be sustained for a long time. A steady and sustained release of silver ions in a concentration level capable of rendering antimicrobial efficacy is a crucial factor for antibacterial materials [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the water molecules in the inter-lamellar regions can change the overall crystalline state of the PA matrix [32]. On the other hand, the release of the substituted Ag + ions in the HA lattice should be much slower [10,20]; this may be another reason why the Ag + release from the Ag-nHA/TiO 2 /PA66 composite scaffold can be sustained for a long time. A steady and sustained release of silver ions in a concentration level capable of rendering antimicrobial efficacy is a crucial factor for antibacterial materials [33].…”
Section: Discussionmentioning
confidence: 99%
“…The nHA (Ca 10 (PO 4 ) 6 (OH) 2 ) slurry with a Ca/P molar ratio of 1.67 was prepared [20]; then, the TiCl 4 solution was slowly dropped into the nHA slurry to form the nHA/TiO 2 slurry. The nHA/TiO 2 precipitate was fully washed with deionized water to remove the chloride ions.…”
Section: Preparation Of An Ag-nha/tio 2 /Pa66 Composite Slurrymentioning
confidence: 99%
See 1 more Smart Citation
“…These problems may be avoided by using metal ions or nanoparticles such as silver, copper, zinc as an antimicrobial agent [7][8][9][10]. In terms of imparting antimicrobial properties to a bone implant, the effect of silver additives in HA [5,6,[11][12][13][14][15][16][17][18][19][20][21] having a strong inhibitory effect on a wide range of bacteria, was studied in more detail. Literature suggests that regardless of the form in which silver is in the implant -either in the form of ions substituting calcium isomorphically, or in the form of nanoparticles located on the surface of HA particles, or in the intergranular space of silver-containing ceramics, to a concentration about 1.5-2 wt.%, the material exhibits excellent bactericidal properties [5,6,11,12].…”
Section: Introductionmentioning
confidence: 99%